How do electronic word of mouth practices contribute to mobile banking adoption?. (January 2020) - Shankar, Amit; Jebarajakirthy, Charles; Ashaduzzaman, Md
Abstract: Mobile banking (m-banking) is the fastest growing and most cost-effective channel for delivering banking services. Electronic word of mouth (eWOM) plays a crucial role in the success of e-commerce. Therefore, the main purpose of this study is to investigate a comprehensive moderated mediated mechanism for enhancing m-banking adoption behavior through positive eWOM triggers using the elaboration likelihood model (ELM). Argument Quality, valence, consistency and volume were considered eWOM triggers, and the conceptual model also included initial trust in m-banking as a mediator and consumer involvement in m-banking as a moderator. A total of 1153 useable surveys completed by the Indian users of social networking websites were used for analysis. The findings showed that of the triggers, argument quality, valence, and consistency enhance intention to adopt m-banking. These effects were mediated by initial trust in m-banking. The mediation effects of initial trust between valence – Intention varied between high and low consumer involvement in m-banking. These findings make several contributions to the literature on marketing communication, particularly to eWOM research and ELM theory. Practically, this study provides several recommendations to banks about how to use positive eWOM for motivating consumers to adopt m-banking. Highlights: Electronic word of mouth (eWOM) plays a crucial role in the success of e-commerce. Using the elaboration likelihood model, this study investigates how positive eWOM triggers impact m-banking adoption intention. Of the triggers, Argument Quality, Valence, and Consistency enhance intention to adopt m-banking. These direct effects are mediated by Initial Trust in m-banking. The mediation effect of Initial Trust between valence and intention is moderated by consumer involvement.